Historical-autobiographical references of the Guacamayas Ecotourism Centerbiocultural heritage in the jungle in Chiapas, Mexico - Barrientos Gutiérrez, Nelly Eblin (2022)
The Guacamayas Ecotourism Center is an important benchmark in Mexico for the biocultural heritage of the jungle in Chiapas. Using a qualitative methodology and an exploratory approach, this work presents a historical-biographical approach to describe its main characteristics. In it we find particularities of its official foundation in 1996, in a natural reserve area of the Chiapas jungle, by a Chinanteco migrant indigenous group that populated this space after the agrarian reform of the 60’s in Mexico. Its cultural legacy, among other factors, made the Center prosper as an enterprise with a sustainable approach. Today the center describes looting and poaching among its threats, while its combat becomes one of its main defining tasks.